INFLUENCE OF EXOGENOUSLY APPLIED AMINO ACIDS ON SOME GROWTH TRAITS AND YIELDS OF THREE WHEAT CULTIVARS (TRITICUM AESTIVUM L.) - I. A. Sarhan; S. I. Neamah (مجلة الأنبار للعلوم الزراعية)
This field study examined the effect of various exogenously applied concentrations of amino acids on some local wheat varieties. The investigation was conducted using a randomized complete block design (RCBD) with three replicates in a split-plot arrangement. The main plots contained amino acid concentrations of 0, 3.0, and 6.0 ml L-1 together with the Iba 99, Al- Rasheed, and Abu Ghraib-3 wheat cultivars in the subplots. The Al-Rasheed cultivar recorded the highest plant height, flag leaf area, spike length and 1000-grain weight with mean values of 111.06 cm2, 44.10 cm2, 14.50 cm2, and 45.00 g, respectively. The Abu Ghraib-3 cultivar had the highest mean number of spikes, grain numbers, grain yield and harvest index at 538.6 spikes m-2, 53.68 grains spike-1, 6.170 ton ha-1, and 35.22%, respectively. Amino acid concentrations significantly affected all growth and yield traits with the 3.0 ml L-1 concentration offering the highest mean value for plant height at 104.69 cm and 513.7 spikes m-2, with the quantity of grains in each spike at 49.98 grains spike-1, total grain yield of 6.023 tons ha-1, and a harvest index of 42.00%. The 6 ml L-1 concentration provided the highest average for flag leaf area, spike length, and 1000-grain weight at 41.89 cm2, 12.30 cm, and 42.00 g., respectively. There was a significant interaction effect between the Al-Rasheed cultivar at the 3 ml L-1 amino acid concentration in plant height and between the Abu Ghraib-3 cultivar in the number of spikes and harvest index. Also, there was an interaction between the Abu Ghraib-3 cultivar at the 6 ml L-1 amino acid concentration and number of seeds per spike